2003
DOI: 10.1292/jvms.65.1331
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenetic Disorders in Adult Rats Exposed to Tributyltin Chloride during Puberty

Abstract: ABSTRACT. Adverse effects of tributyltin (TBT) chloride were investigated on the reproductive system in male adult rats as exposed during puberty. Fifty Sprague-Dawley rats at the age of 35 days were assigned to five different groups: negative control receiving vehicle, methyltestosterone (10 mg/kg B.W.), and TBT chloride treatments (5, 10, and 20 mg/kg B.W.). Animals were treated by oral gavage for ten consecutive days and sacrificed at 5 weeks after final treatment. The treatment of TBT chloride at the high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…Images were recorded in real-time over extended periods. For each slide, the tracks of sperm in 10 fields were recorded for approximately 2-3 min [22]. Centroids were used for estimation of the motion endpoint, which includes motility (number of sperm exceeding threshold minimum velocity/ total number of sperm), curvilinear velocity (VCL: mean frame-to-frame velocity), straight-line velocity (VSL: velocity between centroids in first and last frame tracked), average path velocity (VAP: velocity obtained from smoothing the original path), hyper-activated sperm (HYP), beat cross frequency (BCF: frequency of centroids crossing the average trajectory), mean angular displacement (MAD: time-average of absolute values of the instantaneous turning angle of the sperm head along its curvilinear trajectory), lateral head displacement (ALH: displacement of the centroid from a computer-calculated average trajectory).…”
Section: Analysis Of Sperm Kinematicsmentioning
confidence: 99%
“…Images were recorded in real-time over extended periods. For each slide, the tracks of sperm in 10 fields were recorded for approximately 2-3 min [22]. Centroids were used for estimation of the motion endpoint, which includes motility (number of sperm exceeding threshold minimum velocity/ total number of sperm), curvilinear velocity (VCL: mean frame-to-frame velocity), straight-line velocity (VSL: velocity between centroids in first and last frame tracked), average path velocity (VAP: velocity obtained from smoothing the original path), hyper-activated sperm (HYP), beat cross frequency (BCF: frequency of centroids crossing the average trajectory), mean angular displacement (MAD: time-average of absolute values of the instantaneous turning angle of the sperm head along its curvilinear trajectory), lateral head displacement (ALH: displacement of the centroid from a computer-calculated average trajectory).…”
Section: Analysis Of Sperm Kinematicsmentioning
confidence: 99%
“…Previous studies showed that the sustained exposure to high dose or low dose of TBT reduced spermatogenesis in rat or mice (Omura et al, ; Yu et al, ; Chen et al, ). In addition, exposure to high‐dose TBTCl caused delayed effects on germ count in rat (Yu et al, ). The present study shows that perinatal exposure to low‐dose TBTCl is implicated in causing long lasting alterations in sperm counts and motility.…”
Section: Discussionmentioning
confidence: 95%
“…Tributyltin (TBT), widely used in agriculture and industry, is well known to induce imposex in gastropod mollusks (Smith, 1971;Oetken et al, 2004). Further studies provided evidences that TBT might act as an ED in mammals (Omura et al, 2001;Yu et al, 2003;Grote et al, 2004;Chen et al, 2008;Shi et al, 2009;Si et al, 2011Si et al, , 2012aGraceli et al, 2013). It has been reported that in utero exposure to TBT resulted in increased epididymal adipose mass in adults (Grun et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies addressing the effect of TBT on male reproductive functions have been reported (16,21,(37)(38)(39)(40)(41)(42)(43)(44). A study conducted on male rats over two generations showed that testis, epididymis, ventral prostate, and body weight decreased in all groups, but mainly in the group treated with a dietary concentration of 125 mg TBTCl per g diet (21).…”
Section: Male Reproductive Systemmentioning
confidence: 99%
“…An increase of detached debris and sloughed cells was observed in the tubules of the epididymis and seminal vesicles were narrowed and filled with epithelial cells (42). The count of caudal epididymal and testicular sperm (41) and of homogenization-resistant spermatids decreased (21), and the motility, mean angular displacement, lateral head displacement, and dance of sperm from the vas deferens were also reduced (41).…”
Section: Male Reproductive Systemmentioning
confidence: 99%